2017
DOI: 10.1186/s12954-016-0130-1
|View full text |Cite
|
Sign up to set email alerts
|

The political and scientific challenges in evaluating compulsory drug treatment centers in Southeast Asia

Abstract: BackgroundIn Vietnam, like many countries in Southeast Asia, the commonly used approach of center-based compulsory drug treatment (CCT) has been criticized on human rights ground. Meanwhile, community-based voluntary methadone maintenance treatment (MMT) has been implemented for nearly a decade with promising results. Reform-minded leaders have been seeking empirical evidence of the costs and effectiveness associated with these two main treatment modalities. Conducting evaluations of these treatments, especial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…The Philippine government's approach in criminalising illicit drug use and using fear as a means to get people to stop is also not unique. Asian countries such as Vietnam, China, Cambodia, Indonesia, Malaysia, and Thailand likewise adhere to the philosophy of social reeducation and force people who use illicit drugs into compulsory rehabilitation (Vuong et al, 2017). However, the rise in extra-judicial killings and reports that police receive cash rewards for executing drug suspects (Mogato & Baldwin, 2017) is a critical factor that may affect the success of community-based programs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Philippine government's approach in criminalising illicit drug use and using fear as a means to get people to stop is also not unique. Asian countries such as Vietnam, China, Cambodia, Indonesia, Malaysia, and Thailand likewise adhere to the philosophy of social reeducation and force people who use illicit drugs into compulsory rehabilitation (Vuong et al, 2017). However, the rise in extra-judicial killings and reports that police receive cash rewards for executing drug suspects (Mogato & Baldwin, 2017) is a critical factor that may affect the success of community-based programs.…”
Section: Discussionmentioning
confidence: 99%
“…The Dangerous Drugs Board (2016) of the Philippines reported that 90% of those who have voluntarily surrendered could be treated in the community (Cepeda, 2016). However, like most countries in Asia, the Philippines has primarily employed compulsory residential treatment in resolving illicit drug use problems (Vuong et al, 2017). Given the overwhelming number of clients, communities have created their own programs consisting of community service (e.g., cleaning, beautification, tree planting, gardening), recreational activities (e.g., sports activities, Zumba, yoga), counselling, and spiritual formation (e.g., bible study, prayer groups).…”
mentioning
confidence: 99%
“…Unfortunately, the Philippines did not have a history of community-based drug rehabilitation (CBDR). Like many countries in Asia, illicit drug use was treated primarily using incarceration or through residential treatment (Vuong et al, 2017). With over a million potential clients for CBDR, communities were hard-pressed to develop programs.…”
Section: Case Two: Community-based Drug Recovery Interventionmentioning
confidence: 99%
“…The concordance between self‐reported heroin use and urine drug screens was high (80–86% across four time‐points, see Vuong et al . [31]) indicating that CCT participants reported their heroin use reasonably accurately.…”
Section: Methodsmentioning
confidence: 99%